2007
DOI: 10.1021/la062722v
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Protein Surface Attachment on Untreated and Plasma Immersion Ion Implantation Treated Polystyrene: Protein Islands and Carpet

Abstract: Surface attachment of the enzyme horseradish peroxidase (HRP) was studied on untreated and ion beam implanted polystyrene (PS) films. The PS films of 100 nm thickness on a silicon wafer were treated using the plasma immersion ion implantation (PIII) technique, with argon ions of energy 20 keV and fluences of up to 2 x 10(16) ions/cm2. Differential transmittance Fourier transform infrared (FTIR) spectra confirmed the presence of proteins on the PS surfaces by detection of the amide A, I, and II protein vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 22 publications
8
39
0
Order By: Relevance
“…Similar effects were reported by Nosworthy et al [46]. Covalent immobilization of enzyme horseradish peroxidase with 100% protein coverage on the plasma-modified surface was observed by Gan et al [74] and rapid covalent immobilization of protein molecules on the plasma-modified surface with a larger cell density was observed by Tran et al [60]. Ho et al [75] also observed improved binding of protein molecules with retained conformation and Waterhouse et al [3] observed robust covalent immobilization of protein molecules having low thrombogenicity on the plasma-modified stainless steel coronary stent.…”
Section: CLsupporting
confidence: 85%
“…Similar effects were reported by Nosworthy et al [46]. Covalent immobilization of enzyme horseradish peroxidase with 100% protein coverage on the plasma-modified surface was observed by Gan et al [74] and rapid covalent immobilization of protein molecules on the plasma-modified surface with a larger cell density was observed by Tran et al [60]. Ho et al [75] also observed improved binding of protein molecules with retained conformation and Waterhouse et al [3] observed robust covalent immobilization of protein molecules having low thrombogenicity on the plasma-modified stainless steel coronary stent.…”
Section: CLsupporting
confidence: 85%
“…Rapid covalent binding of protein molecules with a higher cell density on the plasma modified surface was observed by Tran et al [42]. Gan et al [47] observed covalent binding of protein molecules with 100 % coverage on plasma treated surfaces. Waterhouse et al [15] observed good covalent binding of protein molecules with low thrombogenicity on plasma treated stainless steel coronary stents.…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…It interferes with even the strongest interactions involved in physisorption and as such will remove protein that is not covalently bonded to the surface. The SDS cleaning procedure is widely accepted as a method to test whether proteins are covalently attached to surfaces or not 9, 10…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced attachment of bioactive enzymes (horseradish peroxidase, soybean peroxidase, and catalase) on polyethylene, poly(tetrafluoroethylene), and polystyrene treated with plasma immersion ion implantation (PIII) has previously been demonstrated 9–12. These works showed that a significant fraction of the attached protein could not be removed by washing in heated sodium dodecyl sulfate (SDS) solution, which indicated that covalent attachment of the protein molecules to the PIII polymer surface had been achieved without the use of linker molecules or specialized wet chemistry.…”
Section: Introductionmentioning
confidence: 99%